Climate change, ecosystems and abrupt change: science priorities. (27th January 2020) - Turner, Monica G.; Calder, W. John; Cumming, Graeme S.; Hughes, Terry P.; Jentsch, Anke; LaDeau, Shannon L.; Lenton, Timothy M.; Shuman, Bryan N.; Turetsky, Merritt R.; Ratajczak, Zak; Williams, John W.; Williams, A. Park; et al.
Abstract : Ecologists have long studied patterns, directions and tempos of change, but there is a pressing need to extend current understanding to empirical observations of abrupt changes as climate warming accelerates. Abrupt changes in ecological systems (ACES)—changes that are fast in time or fast relative to their drivers—are ubiquitous and increasing in frequency. Powerful theoretical frameworks exist, yet applications in real-world landscapes to detect, explain and anticipate ACES have lagged. We highlight five insights emerging from empirical studies of ACES across diverse ecosystems: (i) ecological systems show ACES in some dimensions but not others; (ii) climate extremes may be more important than mean climate in generating ACES; (iii) interactions among multiple drivers often produce ACES; (iv) contingencies, such as ecological memory, frequency and sequence of disturbances, and spatial context are important; and (v) tipping points are often (but not always) associated with ACES. We suggest research priorities to advance understanding of ACES in the face of climate change. Progress in understanding ACES requires strong integration of scientific approaches (theory, observations, experiments and process-based models) and high-quality empirical data drawn from a diverse array of ecosystems. This article is part of the theme issue 'Climate change and ecosystems: threats, opportunities and solutions'